Adaptation of Organizational Culture in the Implementation of ASN BerAKHLAK Core Values in the Sorong City Government - Rafika, Atika; Hasniati, ‎; Ibrahim, Muhammad Akmal (KnE Social Sciences, 2025)
Organizational culture is related to the values of regulating attitudes and behavior in working. Currently, public organizations are transforming from a hierarchical, rigid work culture and applying the Core Values “BerAKHLAK” namely service oriented, accountable, competent, harmonious, loyal, adaptive, and collaborative, which are the foundation for forming superior ASN behavior, especially in creating a good work culture. This study aims to analyze the extent of the adaptation of organizational culture in the application of the Core Values of the State Civil Apparatus BerAKHLAK in the Sorong City Government. Qualitative research methods are used in this study. Data collection methods include observation, in-depth interviews, and documentation. Data sources consist of primary and secondary data, while data analysis is carried out using interactive methods. The informants in this study were State Civil Apparatus who implemented the ASN BerAKHLAK Core Value in the Sorong City Government. The findings of this study indicate that the implementation of ASN BerAKHLAK core values in the Sorong City Government environment has shown efforts to adapt organizational culture, but its implementation has not been effective. Service-oriented and accountable values have begun to be implemented through more responsive public services, but are still limited to certain regional apparatus organizations. Competent and Loyal face challenges because there are still employees who lack training and motivation. Harmonious and Collaborative values have also not been maximized. Meanwhile, Adaptive as the core of change tends to be hampered by resistance from previous work cultures that have not completely changed.